2017
DOI: 10.1007/s11270-017-3438-x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and Anthropogenic Indicator Inorganics in Urban Stormwater and Snowmelt Runoff: Sources and Mobility Patterns

Abstract: Inorganic chemicals in urban stormwater and snowmelt runoff originate from catchment geology and anthropogenic activities. The occurrence, partitioning and mobility of six minerals and six trace metal (TM) indicators of anthropogenic activities were studied in stormwater, snowmelt and baseflow in four urban catchments, and the sampling of inorganics was supplemented by measurements of electrical conductivity (EC), pH and total suspended solids (TSSs). Minerals occurred at concentrations several orders of magni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…High proportions of many MMs in the suspension along with the dissolved forms of Na, K, Ca, Sr, and Sb were also identified in snow cover on the windward slope of the Salt Lake Valley (central Wasatch Mountains), Utah, USA [111]. The predominance of suspended forms of most MMs seems to be typical of urban areas, as supported by the data on Cr, Pb, Cu, Ni, Al, and Fe in snow in Östersund [15] and on Pb, Cu, Zn, and Cd in snow in Luleå and Umeå, Sweden [16]. Concentrations of Al, Fe, Mn, and V in snow cover of the traffic zone increase with increasing particle size reaching the maximum in particles >1000 µm, while the concentrations of Zn and Pb are the highest in particles < 100 µm [21].…”
Section: Partitioning Of Mmssupporting
confidence: 53%
See 1 more Smart Citation
“…High proportions of many MMs in the suspension along with the dissolved forms of Na, K, Ca, Sr, and Sb were also identified in snow cover on the windward slope of the Salt Lake Valley (central Wasatch Mountains), Utah, USA [111]. The predominance of suspended forms of most MMs seems to be typical of urban areas, as supported by the data on Cr, Pb, Cu, Ni, Al, and Fe in snow in Östersund [15] and on Pb, Cu, Zn, and Cd in snow in Luleå and Umeå, Sweden [16]. Concentrations of Al, Fe, Mn, and V in snow cover of the traffic zone increase with increasing particle size reaching the maximum in particles >1000 µm, while the concentrations of Zn and Pb are the highest in particles < 100 µm [21].…”
Section: Partitioning Of Mmssupporting
confidence: 53%
“…Medium roads, similar to the MRR, are characterized by a significant proportion (>80%) of suspended forms for Sn, Ti, Bi, Al, W, Fe, Pb, V, Cr, and Mo and relatively low ones for Zn and Cd (43% and 31%, respectively). A high proportion of dissolved Zn reaching 70% is typical of traffic area runoff [14], and of dissolved Cd and Zn for snowmelt water, in which the solubility of these metals could reach 100% and 81%, respectively [15]. The ratio of MMs forms on large, small roads, and highways is scarcely different from the average level for all WAO roads.…”
Section: Partitioning Of Mmsmentioning
confidence: 99%
“…Concentrations of Cd, Cu, Cr, Pb and Zn were found to regularly exceed environmental targets in Australian streams receiving urban stormwater (Allinson et al, 2017). Galfi et al (2017) found that trace metal fluxes from four urban watersheds in Sweden mirrored that of TSS, indicating predominant transport in the particulate rather than dissolved phase. Furthermore, snowmelt was identified as a more important source of trace metals than rain-driven runoff in this study, likely due to the longer time for metal accumulation.…”
Section: General Stormwatermentioning
confidence: 91%
“…While coal, oil and gas generation have been the primary focus of research on how landscapes may change, pipeline operations have received less attention. However, over recent years, oil and gas pipelines have undergone substantial expansion globally [1]. This is connected with the quest for energy security and the development of reliable transnational energy sources.…”
Section: Introductionmentioning
confidence: 99%